KESERAGAMAN DAN PANCARAN IRIGASI PIPA PERFORASI PADA BERBAGAI KEMIRINGAN PIPA TRANSMISI - I Dewa Gede Jaya Negara; Humairo Saidah; I Wayan Yasa; Adhitya Halim .P (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
The potential of hilly dry land needs to be developed for limited land farming to have an equal distribution of food security in various potential areas. Many existing drylands, especially in hilly and sloping areas, have not been managed optimally for agriculture due to limited support for practical irrigation techniques. Utilizing differences in existing land elevation is a potential that can be exploited by irrigation techniques that require water pressure. The perforated pipe system irrigation technique has similarities to the mini sprinkler system because it uses water pressure, and it is very possible to be applied to sloped land conditions, but the ability of the perforation system needs to be known further so that it can be used for practical irrigation. For this reason, it is necessary to test the perforated irrigation system with certain variations of the slope of the beam range and uniformity, so that later it can be used as an initial reference. The test model uses a water source from a tendon as high as 3.7 m and with a tank capacity of ± 200 liters. The diameter of the transmission pipe is ½ inch with a length of 2.55 meters, and the lateral pipe as a perforation pipe with a 3mm hole consists of 3 pipes with a pipe length of 4 meters with a diameter of 1/2 inch and the distance between the holes of the perforation pipe is 60 cm. The test was carried out on 4 variations of the slope of 10º, 20º, 30º, and 40º with 4 variations of head 1 = 2.855 m, head 2 = 2.35 m, head 3 = 1.85 m, and head 4 = 1.30 m. Based on the research results, it shows that the greater the slope of the transmission pipe, the higher the head will be. The uniformity of the perforation irrigation was getting smaller the larger the slope with a minimum value of 85% and the highest being 91%. A large perforation beam is obtained at transmission slopes of 20º and 30º, namely 2.66 m and 2.40 m.